In silico analysis of hypothetical proteins in Pseudomonas aeruginosa PAC1: Structural and functional insights - Mutaz Mohammed Abdallah; Ruaa Abdalla Ibrahim Suliman; Yousra Tagelsir Ahmed; Mawada Yahia (Journal of Genetic Engineering and Biotechnology)
Background: Bacterial genomes contain numerous hypothetical proteins (HPs) with uncharacterized roles. This study used computational methods to identify and predict the functions of such proteins in the Pseudomonas aeruginosa PAC1 strain. Methods: The PAC1 genome (GenBank: CP053706.1) was analyzed, starting with 828 HPs. Proteins shorter than 50 amino acids (unlikely to form stable structures) were excluded, leaving 807 HPs. Physicochemical properties were assessed to filter unstable proteins, resulting in 272 candidates. Subcellular localization tools predicted cytoplasmic localization for 58 proteins. Functional annotation identified conserved domains, and homology modeling generated 3D structures for proteins with >80 % similarity to known templates. Structural validation and active site prediction were performed to assess biological relevance. Results: Two HPs, WP_003099663.1 (186 residues) and WP_010793930.1 (455 residues), exhibited structural stability and functional potential. WP_003099663.1 was annotated as a zinc-dependent enzyme involved in carbon dioxide regulation, while WP_010793930.1 was linked to amino acid biosynthesis. Structural models confirmed stable folds, and ligand-binding site predictions highlighted conserved regions, suggesting roles in metabolic pathways. Conclusion: This study demonstrates a systematic computational approach for characterizing hypothetical proteins in bacterial genomes. WP_003099663.1 and WP_010793930.1 exhibit promising structural and functional features and warrant further experimental investigation.